Which Truth? How to Overcome a Post-Truth Society (KULT_online, 2020)
In Post-Truth, Scepticism & Power Stuart Sim, a critical theorist and strong believer in a liberal democracy, examines the many different realms of society in which post-truth plays a role. This spans a historical outline of the history of truth, political and philosophical discussions, and several very fitting examples to underline the theories. Sim thematizes different strategies to counter post-truth. Sim admits that truth is a difficult concept, but it needs to be the basis of democracy.